From Scroll to Checkout: Generation Z's Lived Experiences with TikTok Content Marketing - Lily Harlina Putri; Trenggono Pujo Sakti (Talenta Publisher, 2026)
TikTok has transformed digital marketing by enabling interactive and personalized consumer–brand engagement. Although previous studies have linked content marketing, brand awareness, social proof, and purchase decisions, little is known about how Generation Z experiences these processes. This study explores Generation Z's lived experiences of TikTok content marketing using an interpretative phenomenological approach. Semi-structured interviews were conducted with 20 Generation Z consumers, and the data were analyzed using the Gioia methodology. The findings identify a sequential consumer experiential journey comprising TikTok Content Marketing Types, Formation of Brand Awareness, Social Proof as a Trust Builder, The Purchase Decision Process, and Reflection of Consumer Experience among Generation Z. Authentic content stimulates initial engagement, repeated algorithm-driven exposure enhances brand awareness, social proof strengthens trust, and purchase decisions result from rational evaluations supported by community validation. Repeated interactions also foster digital reflexivity, encouraging consumers to critically evaluate marketing information before purchasing. This study contributes to digital marketing literature by proposing a phenomenological model explaining how TikTok content experiences shape Generation Z's purchasing behavior within the social commerce ecosystem.